Celt production processes and loci in Neolithic Greece - Anna Stroulia; Tasos Bekiaris; Christos L. Stergiou; Vasilios Melfos (Documenta Praehistorica)
For reasons pertaining more to aesthetics than frequencies, celts represent the most studied macrolithic, i.e. ground stone, type from Neolithic Greece. Reports of varying length and thoroughness are available for roughly 50 assemblages. Due to archaeological biases, however, these assemblages are not evenly distributed geographically. Most derive from the regions of Macedonia and Thessaly, with other areas represented minimally or not at all. Equally important, research has shed light on the related types of raw material and acquisition methods, manufacturing techniques, aspects of use, practices of discard, as well as non-utilitarian dimensions. However, very little is known about the whereabouts of celt production. In this paper, we attempt to address both gaps by turning our attention to the northeastern region of Thrace and focusing on the celts excavated at the Middle-Late Neolithic tell site of Makri. We discuss these tools’ forms, lithologies, and chaînes opératoires, revisit a structure identified by the excavators as a ‘celt workshop’, bring in relevant data from other sites, and, last but not least, problematize the celt workshop concept itself.